2017
DOI: 10.1016/j.jagp.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder among Older Adults Experiencing Motor Vehicle Collision: A Multicenter Prospective Cohort Study

Abstract: Objective To characterize risk factors for and consequences of posttraumatic stress disorder (PTSD) among older adults evaluated in the emergency department (ED) following motor vehicle collision (MVC). Design Prospective multicenter longitudinal study (2011–2015). Setting 9 EDs across the United States. Participants Adults aged 65 years and older who presented to an ED after MVC without severe injuries. Measurements PTSD symptoms were assessed 6 months after the ED visit using the Impact of Event Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Seventy-two percent of patients reported at least one positive PTSD symptom at 30 days (defined as a score of 2 or more on at least one PCL-5 question), and 25% reported clinically significant PTSD symptoms (defined as scored 2 or more on at least one B item [questions 1-5], one C item [questions 6 and 7], two D items [questions [8][9][10][11][12][13][14], or two E items [questions [15][16][17][18][19][20] or a total score greater than 32). 19,20 Among the entire cohort the median (IQR) PCL-5 score was 7 (0 to 30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy-two percent of patients reported at least one positive PTSD symptom at 30 days (defined as a score of 2 or more on at least one PCL-5 question), and 25% reported clinically significant PTSD symptoms (defined as scored 2 or more on at least one B item [questions 1-5], one C item [questions 6 and 7], two D items [questions [8][9][10][11][12][13][14], or two E items [questions [15][16][17][18][19][20] or a total score greater than 32). 19,20 Among the entire cohort the median (IQR) PCL-5 score was 7 (0 to 30).…”
Section: Resultsmentioning
confidence: 99%
“…Perceived threat (conceptualized as a self‐measured sense of life endangerment and personal vulnerability) has previously been described as a contributor to the development of traumatic injury–induced PTSD (e.g., after motor vehicle crash or military‐related trauma) . The Trauma Recovery Project, a large multicenter epidemiologic study, cites perceived threat to life as a significant predictor of PTSD symptoms among patients experiencing traumatic injury .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A prospective validation study of field triage processes showed that half of seriously injured older adults are missed by the guidelines and transported to non-trauma centers. 5 Because older adults are a particularly vulnerable population with high morbidity and mortality following injury, [7][8][9][10][11] developing better methods for the early identification of high-risk patients is a major priority for field triage.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, a study to categorize risk factors and effects of PTSD in older adults after motor vehicle accidents found that PTSD symptoms were significantly associated with adverse health outcomes. 6 Stressors such as witnessing death, serious injury, or sexual violence may be relived in the form of flashbacks or nightmares accompanied by persistent anxiety, depression, and physical reactivity and may result in severe disabilities in psychological, social, and occupational wellbeing. 7 A diagnosis of PTSD may be made if several specific criteria are met as per the diagnostic criteria set in the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV), and appropriate and timely treatment can significantly improve the patient's prognosis.…”
Section: Introductionmentioning
confidence: 99%